A 60 Year Record of Atmospheric Aerosol Depositions Preserved in a High‐Accumulation Dome Ice Core, Southeast Greenland. Issue 1 (4th January 2018) - Iizuka, Yoshinori; Uemura, Ryu; Fujita, Koji; Hattori, Shohei; Seki, Osamu; Miyamoto, Chihiro; Suzuki, Toshitaka; Yoshida, Naohiro; Motoyama, Hideaki; Matoba, Sumito
Abstract: The Southeastern Greenland Dome (SE‐Dome) has both a high elevation and a high accumulation rate (1.01 m we yr −1 ), which are suitable properties for reconstructing past environmental changes with a high time resolution. For this study, we measured the major ion fluxes in a 90 m ice core drilled from the SE‐Dome region in 2015 and present the records of annual ion fluxes from 1957 to 2014. From 1970 to 2010, the trend of nonsea‐salt (nss) SO4 2− flux decreases, whereas that for NH4 + increases, tracking well with the anthropogenic SO x and NH3 emissions mainly from North America. The result suggests that these fluxes reflect histories of the anthropogenic SO x and NH3 emissions. In contrast, the decadal trend of NO3 − flux differs from the decreasing trend of anthropogenic NO x emissions. Although the cause of this discrepancy remains unclear, it may be related to changes in particle formation processes and chemical scavenging rates caused by an increase in sea salt and dust and/or a decrease in nssSO4 2− . We also find a high average NO3 − flux (1.13 mmol m −2  yr −1 ) in the ice core, which suggests a negligible effect from postdepositional NO3 − loss. Thus, the SE‐Dome region is an excellent location for reconstructing nitrate fluxes. Over a decadal time scale, our NO3 − flux record is similar to those from other ice cores in Greenland high‐elevation sites, suggesting that NO3 − concentration records from these ice cores are reliable. Key Points: A Greenland ice core from a high‐accumulation area records the seasonal ion fluxes over the past 60 years without postdepositional effect Sea salt and dust fluxes increased after 2000, indicating increased contribution of local regions in Greenland and around the ocean Sulfate flux responds to the decreasing trend of SO x emissions, but the nitrate flux does not follow the decrease in NO x